Penguatan Reformasi Sektor Keamanan Di Wilayah Perbatasan (Border) Indonesia - Asyono, Abimanyu Hendi (Jurnal Kajian Stratejik Ketahanan Nasional, 2020)
The implementation of Security Sector Reform in the context of security and supervision in Indonesia's border areas still has a lot of homework that needs to be done, both in terms of regulations and institutions. In addition to the multidimensional sources of threat, the operational institutions of the Border Agency components (Customs and Excise, TNI, Polri, National Border Management Agency (BNPP) and immigration) still seem to work in a sectoral, overlapping, and not cross integrated manner. sector, which of course in carrying out their duties there will be clashes and conflicts of interest from each of these institutions. The handling of potentially corrupt Border Agency officers is also a very decisive factor in the occurrence of a potential national security threat in the border area. Strengthening the Concept of Security Sector Reform based on Integrated Border Management (IBM) offers new hope in the context of solving problems and dynamics of threats in the territory of Indonesia. The advantages offered by IBM are guarantees that the Border Agency or the authorized parties in their duties and functions to carry out supervision, service, and security in the Indonesian border areas, will be able to work together with the same vision and mission through the application of cross-sectoral integration, in order to facilitate movement of people and goods across national borders. IBM also guarantees that on all coasts of the Indonesian border, surveillance, service and security activities in the Indonesian border areas will be carried out with the same method, method and quality wherever the border is located. Keywords: Security Reform, Integrated Border Management Sector, Border Agency, Border Security